Enhancing Microwave Absorbing Properties of Nickel-ZincFerrite with Multiwalled Carbon Nanotubes (MWCNT) Loading at Higher Gigahertz Frequency - Fadzidah Mohd Idris; Khamirul Amin Matori; Ismayadi Ismail; Idza Riati Ibrahim; Rodziah Nazlan; Mohd Shamsul Ezzad Shafie (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology